2019
DOI: 10.1159/000497821
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Attenuates Adriamycin-Induced Focal Segmental Glomerulosclerosis by Inhibiting the Hypoxia-Inducible Factor-1α Expression Through Phosphatidylinositol 3-Kinase/Protein Kinase B Pathway

Abstract: Background: Focal segmental glomerulosclerosis (FSGS) is a common histologic pattern of kidney injury, which may eventually lead to end-stage renal disease. Objectives: Salidroside (SAL, p-hydroxyphenyl-β-D-glucoside) is an active component isolated from Rhodiolarosea, which has various pharmacological properties including anti-inflammation and antioxidation. SAL may attenuate FSGS, but the underlying mechanism is not clear. Thus, in this study, we focus on the renoprotective role of SAL in FSGS using Adriamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…In the present study, we been found that cells treated with IL-1b had significantly increased levels of p-PI3K and p-AKT. Previous studies have reported that Salidroside has a negative effect on PI3K/AKT activation [12]. Our data are consistent with previous studies reporting that Salidroside blocks the IL-1 b-induced PI3K/AKT activation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we been found that cells treated with IL-1b had significantly increased levels of p-PI3K and p-AKT. Previous studies have reported that Salidroside has a negative effect on PI3K/AKT activation [12]. Our data are consistent with previous studies reporting that Salidroside blocks the IL-1 b-induced PI3K/AKT activation.…”
Section: Discussionsupporting
confidence: 93%
“…Salidroside, the major constituent of a Chinese medicinal herb, Rhodiola rosea L, has been reported to suppress apoptosis in many diseases [11]. Its anti-inflammation effect works on Adriamycin-induced focal segmental glomerulosclerosis through suppressing the PI3K/AKT pathway [12]. Considering its various beneficial effects, Salidroside is thought to protect chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…As anucleated cells, platelets also express AKT which involves in regulating platelet function, such as platelet aggregation, activation, granule secretion as well as integrin signaling [42,43]. Through inhibition of PI3K/AKT signaling pathway, salidroside have been shown to repress proliferation, migration and invasion of human lung cancer cells [29], induce autophagy in human colorectal cancer cells [28] suppress LPSinduced myocardial injury [44] as well as attenuate Adriamycin-induced focal segmental glomerulosclerosis [45]. Consistent with these, in our present study, we demonstrated that salidroside treatment significantly reduced the phosphorylation of AKT (Thr308/Ser473) AGING after stimulation with thrombin in both human and mouse platelets, indicating that salidroside exerts antiplatelet activities possibly through inhibition of AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MI/R injury is closely related to oxygen-free radical accumulation and mitochondrial dynamics disorder, affecting myocardial cell proliferation and apoptosis [ 13 , 14 ]. MiR-21 can repair MI/R injury by affecting reactive oxygen species (ROS)-mediated oxidative stress [ 15 , 16 ]. Programmed cell death protein 4 (PDCD4) is an important tumor suppressor that plays a vital role in cellular oxidative stress.…”
Section: Introductionmentioning
confidence: 99%